Avaliação de modelos matemáticos para dimensionamento do bulbo molhado na irrigação por gotejamento - Sato, Lucas Massayuki (Universidade Federal de São Carlos, 2012)
The increasing current demand of water has caused conflicts between their multiple uses, being the agriculture responsible for the use of the largest portion of this natural resource. In this context, drip irrigation has shown growth in irrigated area due to their potential to achieve high efficiency in water application. Drip irrigation is characterized by the application of small volumes of water at high frequency directly in the root zone of plants, helping to maintain soil moisture near field capacity in a given volume of soil usually called the wet bulb. Knowing the dimensions of the wetted generated to be used in drip irrigation project is of fundamental importance for the proper design and operation of drip irrigation systems. The objective of this study was to test the performance of the mathematical models Schwartzman and Zur Reprinted and HYDRUS-2D in predicting dimensions of wet bulb generated generated by emitters of different flow flow rates. In its first part, held at the experimental field of Taubate University, were collected the dimensions of the wet bulbs generated by drip of 2, 4 and 8 L h-1 in a dystrophic red-yellow. In the second, were simulated the dimensions of wet bulb using Schwartzman and Zur Reprinted and HYDRUS-2D models. Statistical analysis used to evaluate the performance of these models have shown that the model Schwartzman Zur Reproduced predicted the experimental data set with an accuracy of 94%, whereas in the case of model HYDRUS-2D, this accuracy was 85%. It was concluded that the two studied models can adequately estimate the dimensions of the wet bulb, for the studied conditions, highlighting, however, that the model performed better was Schwartzman-Zur Reprinted.
Evaluation of mathematical models for wet bulb design in drip irrigation
Keywords: Irrigação; Modelos matemáticos (Simulação matemática); Irrigação localizada; Reflectometria no domínio do tempo (TDR); Irrigation management; Mathematical simulation; Irrigation; TDR probe; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO::IRRIGACAO E DRENAGEM